P275 Prevalence and Treatment of Active Asthma in Scotland Using the Prescribing Information System. (19th November 2012) - Steiner, MFC; Devereux, G; Turner, SW; McLay, J; Bishop, I; Wyper, G
Abstract : Background: Many studies of the clinical epidemiology of asthma that have used routinely collected drug prescription or dispensing data have been limited to samples assumed to be representative of the national population from which they are drawn. Our aim was to describe asthma prevalence and treatment in children and young adults using the Prescribing Information System (PIS), a national prescribing and dispensing database for Scotland. Methods: For more than 95% of the dispensed prescriptions in primary care between December 2009 and November 2011 a valid patient identifier was available and the database includes some socio-demographical characteristics (age-group, sex, SIMD) of the patients. Data were also linked to hospital admission data. The analysis was limited to patients aged up to 44 years to reduce contamination by COPD. Data We identified 358, 804 patients with 2, 809, 563 dispensed prescriptions for inhaled therapies used for asthma; equating to a prevalence of 11.4% of the 3, 139, 356 people aged 0–44 registered with a GP in Scotland. The age specific prevalence rates are detailed in the table. However, 95, 207 patients had only one or two dispensed prescriptions for short-acting beta2-agonists (SABA) and no other inhaled therapies in the two years; we consider these patients to be unlikely to have active asthma (table ). Additionally, 1, 041 cases on inhaled therapy had hospital admission(s) with a diagnosis of COPD (ICD10: J40-J44) and are excluded from further analysis. 6, 056 (2.3%) of people collecting inhaled therapy (>2 SABA) had at least one hospital admission with a primary diagnosis of asthma. 18.4% of patients collected SABA only, 46.8% collected SABA + inhaled corticosteroids (ICS), 0.1% (371) collected SABA +long acting beta2 agonist (LABA) only, 13.6% collected SABA +combined ICS/LABA preparation, 2.1% collected SABA + ICS +LABA, 1.7% collected ICS/LABA only, leukotriene receptor antagonists (LTRA) were collected by 8.1% and long acting antimuscarinic agents (LAMA) were collected by 1.0%. Conclusion: This current and whole population database indicates that the prevalence of asthma is approximately 10% in young adults and 15% in children living in Scotland but prevalence of active asthma is approximately 8% in adults and 10% in children.